The Effect of Counseling on The Importance of Balanced Nutrition Through Poster Media on Breakfast Habits of Students at SDN 155 Gresik - Hilda Vilatul Rohmin; Inne Soesanti; Taufiqurrahman; Mujayanto (Journal of Nutrition Explorations, 2024)
Balanced Nutrition Message recommends getting used to breakfast. If you don't have breakfast, your concentration will be disturbed and your learning achievement will drop. Counseling is carried out to improve a person's behavior with messages conveyed through print media (posters) the aim is to change students' breakfast habits. In order to observe students' breakfast habits, this research used a pre-experimental study with a one group pretest posttest design. A total of 40 children participated in the study at SDN 155 Gresik in grades 4 and 5, using the proportional random sampling method. The average knowledge score before and after counseling was 61.35 78.50. Breakfast behaviors were graded on a scale from 75.58 to 81.55 before and after counseling. According to the study's findings utilizing the paired t-test, balanced nutrition counseling through poster media had an impact on understanding of balanced nutrition (p 0.05), but had no impact on breakfast behaviors (p > 0.05). It is preferable to implement balanced nutrition advice, and one of them is establishing a breakfast routine because it can stimulate the brain and aid in concentration and focus while learning.